2017
DOI: 10.1080/09688080.2017.1381533
|View full text |Cite
|
Sign up to set email alerts
|

Women’s satisfaction and perception of control in childbirth in three Arab countries

Abstract: Women's satisfaction and perceived control in childbirth are important attributes of the childbirth experience and quality of care indicators. This article presents findings from the pre-intervention phase of a multi-centre implementation study in Egypt, Lebanon and Syria, to introduce a labour companionship model in these countries. A sample of 2620 women giving birth in three public teaching hospitals from November 2014 to July 2015 in Beirut and Mansoura, and from November 2014 to April 2015 in Damascus wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
1
38
0
3
Order By: Relevance
“…It is a 34‐item, five‐point Likert scale, with six subdimensions addressing self, partner, baby, nurse/midwife, physician and a general rating scale . It was translated to Arabic and adapted to a 31‐item scale ; (iii) The shortened 10‐item Labour Agentry Scale (LAS) with seven‐point Likert scale was used to assess women's perception of control during labour . The scale was translated to Arabic and back‐translated to English.…”
Section: Methodsmentioning
confidence: 99%
“…It is a 34‐item, five‐point Likert scale, with six subdimensions addressing self, partner, baby, nurse/midwife, physician and a general rating scale . It was translated to Arabic and adapted to a 31‐item scale ; (iii) The shortened 10‐item Labour Agentry Scale (LAS) with seven‐point Likert scale was used to assess women's perception of control during labour . The scale was translated to Arabic and back‐translated to English.…”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 Previous studies on patient satisfaction show that factors that influence client satisfaction with regard to care involve satisfaction with the overall health service, health workers’ communication, health workers’ attitude and the hospital environment. 5 , 6 Many countries, including South Africa, have therefore designed strategies that focus on patients’ needs and better communication to improve patient satisfaction. One of the strategies implemented in South Africa to achieve this was the introduction of the Bath-Pele principles.…”
Section: Introductionmentioning
confidence: 99%
“…Women should be encouraged to give birth in a position they deem comfortable (Nieuwenhuijze et al, 2013 study showed very low satisfaction (34%) with this factor (Takács & Seidlerová, 2013). In a study by Kabakian-Khasholian et al (2017), a high level of satisfaction with childbirth and an average level of control perception were demonstrated. Similarly, maternal control was identified as the most important predictor of birth satisfaction in the study by Nilsson et al (2013).…”
Section: Discussionmentioning
confidence: 97%